#TITLE_ALTERNATIVE# - DANIEL SEMBIRING (NIM 23295034) ; Pembimbing: Adang Suwandi A.,Dr., Ir., AKHMAD
The existing moving objects position tracking and information monitoring system (which rely on voice communication via radio) has many disadvantages. This disadvantages are mainly caused inexistance of the acurate and precise last position information of the monitored moving objects. In this thesis, a system that can track the position and monitor the status information of moving objects is designed and implemented. The main focus of the research in theis thesis is to design and implement suchsystem using GPS (global positioning system) dan packet radio technology. In this designed system, position data is retrieved from a GPS receiver, and information status data (which can by used as a telemetry system) is read from an input port at a modul in the moving object. Position and status information data is sent periodically by the moving unit to the monitoring unit through a radio media with packet radio technology which makes it possible to track and monitor more thar one moving object at a time simultanously. In general, the system that has been designed and implemented works fine and met the specification. There is an inexact position tracking which is caused by GPS receiver's precision level and the digital map resolution. To improve the system level of precicion, error correction such as pseudo-differential GPS can be applied.